Low-power Wireless Security System in the Home Automation - Thang, Pham Manh (VNU Journal of Science: Mathematics - Physics; Vol 29 No 1, 2013)
Abstract: Wired networking has been used in home automation for many years and proven to be reliable. Wireless has only recently become a viable option for home automation thanks to improved reliability and reduced cost. Today there are many scenarios where wireless is a viable and preferable option, such as hard-to-wire or expensive-to-wire locations, interconnecting multiple buildings, and need for mobility. The home automation system is usually installed in building that monitors and controls devices like environment and energy managing, appliances switching, fire alarming as well as access and security controlling. For design the hardware of wireless security system, the electronic component CC1101 of Texas Instruments has been selected as the core of the device RF receiver / transmitter with frequency 433 Mhz. This is a modern component, low-cost, low power and it was designed specifically for wireless applications and suitable for connection control devices in the home automation. This idea has been being realized at a project KC03.DA12/11-15 in theUniversityofEngineeringandTechnology,VietnamNational University inHanoi. Keywords: Wireless networking, building automation, RF transmitter, microcontroller, SPI interface.